THE MODERATING ROLE OF ENVIRONMENTAL CONCERNS AND TRUST TOWARDS AN ORGANIC PRODUCT - Sumathy, M.; Rathna, G.Anitha; Ramya, B. (The journal of contemporary issues in business and government, 2021)
Now a days consumers are preferred to consumes an organic has risen over an time, it may shows an positive attitude towards these organic product, but in an research suggest comparatively low volume of an Consumption in the markets. This has resulted to study motivation to enhance a consumer tendency to choose to purchase organic foods. This research attempt to understand a potential association between Motivation, buying behaviour and attitude towards on organic products. To develop a theoretically framework by using an SDT (Self - Determination Theory) which is used to evaluate an organic Consumers. The data was analyzed through a Structural Equational Model (SEM), attitude and consumer behaviors are used to find out an consumer motivation to purchase an organic foods. According to an SDT there are various kinds of a motivational factors influencean consumer like intrinsic motivation, Integrated regulation, Integrated regulation and Extrinsic motivation. Researcher find out a there is an association between Introjection Motivation and Identified motivation are mostly influence them to purchase am organic foods.